A coherent approach for cation surface diffusion in clay minerals and cation sorption models: Diffusion of Cs+ and Eu3+ in compacted illite as case examples. (1st April 2020) - Glaus, M.A.; Frick, S.; Van Loon, L.R.
Abstract: The conceptual setup and the parametrisation of surface diffusion models for different types of cations in negatively charged clay minerals has still not been fully developed. In particular, the contribution of different types of surface-associated cationic species to the overall mass transfer rates is an open question. Further, the transferability of sorption data gained on dispersed clay suspensions to the compacted clay minerals or consolidated clay rocks remains also unanswered. This contribution presents experimental results for the diffusion of 134 Cs + and 152 Eu 3+ in and sorption on compacted illite (bulk-dry densities of 1900 and 1700 kg m −3, respectively) and their interpretation using thermodynamic and transport modelling. Different solution parameters, such as pH, ionic strength and the concentration of stable isotope background were varied. The results give information on both diffusional processes of the two radionuclides and their sorption behaviour at relevant solid-to-liquid ratios. The existing two site protolysis non electrostatic surface complexation and cation exchange (2SPNE-SC/CE) model turned out to be fully valid for the description of the equilibrium distribution of the test cations between the solution and the clay phase in the compacted state. The model had to be extended by an electrical double layer description of cationic species bound to the planar surfaces, involving mobile species in the diffuse layer, in order to successfully model the observed diffusion profiles. Despite the notable differences in sorption behaviour of Cs + and Eu 3+ on illite, their diffusional behaviour could thus be satisfyingly described using the same model approach.